Textuality of a tragedy, analysis of the photographic image of the fotonovela “Vivir o Morir” a social project of the Editorial Quimantú - Arros-Aravena, Alejandro (2022)
The text, Vivir o Morir, by the Chilean writer Alfonso Alcalde, has a prolific work, where the visually supported journalistic report stands out fundamentally, and it is through a method of analysis called the lowest common visual denominator M.C.D.V. The relevance of the images with the supporting text has been submitted, for which 65 participants have been exposed to the observation of images where four attributes related to the emotions associated with photographic taking were classified. In conclusion, it has been determined through the exposure of images that these young university students are influenced by these images, especially when an affective emotional bond of cultural origin is established.